Factors Influencing Chinese Internet Users’ Participation in Short Video App Governance: Implications for Sports Content and Community Engagement - Chen Zhang; Xiaoni Zhu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The increasing popularity of short video platforms among Chinese users has led to the proliferation of sports-related content, which often includes issues such as intellectual property infringement, inappropriate behavior, and misinformation, highlighting the urgent need for effective governance. Users play a critical role as key stakeholders in these platforms' governance. However, limited research has explored the factors influencing Chinese internet users' intention to participate in governance behaviors on short video apps, particularly in the context of sports content and community engagement. This study extends the Norm-Activation Model (NAM) by incorporating Internet ecological perception variables and employing reward and punishment factors as moderating variables to form an enhanced framework. Based on 383 valid responses analyzed using structural equation modeling and hierarchical regression, the findings reveal that personal norms significantly influence users' intention to engage in governance behaviors. These norms are shaped by consequence awareness and responsibility attribution, both of which are positively impacted by users' ecological perception of the Internet. Additionally, the study highlights the mediating role of personal norms and the moderating effect of rewards and punishments in strengthening users' behavioral intentions. The results suggest that raising awareness of the negative consequences associated with unethical or harmful sports-related content can enhance users' sense of accountability. Moreover, incorporating extrinsic motivational factors such as rewards and penalties can further stimulate active participation in governance. This research offers valuable insights into fostering ethical behavior, promoting community engagement, and ensuring the quality of sports content on short video platforms, contributing to a healthier and more responsible digital sports ecosystem.